Diagnostic dilemma in left flank mass in an infant: A rare case of intrarenal neuroblastoma - Ashish Kaushik; Poonam Sherwani; Saurya; Deepak Kumar Garnaik (African Journal of Paediatric Surgery, 2023)
Neuroblastoma (NBL) and nephroblastoma present with abdominal mass and various imaging features help in differentiating the two; however, localisation is difficult in large masses and at times imaging features can be confusing. Here, we describe the case of large left-sided NBL arising from the adrenal and involving the left kidney with moderate hydronephrosis.